Water Limits Radial Tree Growth More Than Light in an Everwet Subtropical Forest - Laura E. Boeschoten; Chris M. Smith‐Martin; Jose A. Medina‐Vega; Kristina J. Anderson‐Teixeira; Luis A. Esbrí Ruiz; Rebecca A. Montgomery; Monique Picón; Mukund P. Rao; Tana E. Wood; Xiangtao Xu; Jess K. Zimmerman; María Uriarte (Global Change Biology, 2026)
Everwet tropical forests, defined by the absence of a pronounced dry season, are globally significant carbon sinks, covering roughly 80% of Southeast Asian tropical forests, 30% of the Amazon basin, and 10% of the Congo Basin. Yet the climatic drivers of stem radial growth in these ecosystems remain understudied. The prevailing hypothesis is that growth is primarily light‐limited, as persistent cloud cover constrains photosynthesis. Evaluating this assumption is critical as climate projections for the humid tropics point towards rising atmospheric evaporative demand, episodic drought, and reduced cloud cover, conditions whose net effect on woody growth remains unresolved. To address this gap, we deployed automated point dendrometers on 35 trees in an everwet subtropical forest with 3500 mm mean annual precipitation and no pronounced rainfall seasonality, collecting 2 years of hourly radial stem growth data alongside concurrent measurements of soil moisture, vapor pressure deficit (VPD), and light availability. Contrary to the prevailing light‐limitation hypothesis, soil moisture and atmospheric evaporative demand were the primary determinants of both whether and how much growth occurred on any given day, even under these perennially wet conditions. Light availability and photoperiod enhanced growth magnitude when water was not limiting, but their effects were consistently smaller. Droughts occurring during the wetter, high‐growth months had the greatest negative impact on annual stem increment, potentially reducing annual growth to just 20% of current levels. These results challenge long‐standing assumptions of light‐limited stem growth in everwet forests, which is critical for improving model projections of forest responses to climate change. Broader validation across tropical forests, combined with direct physiological measurements of carbon uptake and storage, will be essential to evaluate our working hypothesis that radial growth in these everwet ecosystems is ultimately more constrained by water availability than by carbon supply.